SUPPLY CHAIN INTEGRATION AND ITS IMPACT ON THE PERFORMANCE OF THE OPERATIONS MANAGEMENT SYSTEM-AN EXPLORATORY STUDY IN THE IRAQI FERTILIZER COMPANY, SOUTHERN REGION - Manal Abdul Hamid Abdul Majeed (Scholars Digest Publishing, 2024)
The vision and mission of any company is determined by how interaction will be created between the organization’s resources and then transformed into goods and services with the aim of conforming to design specifications on the one hand and achieving consumer satisfaction on the other hand. Therefore, the study aims to provide the company with useful information that supports the performance of the operations system in order to focus on Activities that add value to the product on the one hand and reduce waste and costs on the other hand. The study was conducted at the General Fertilizer Company / Southern Region through a field study and collecting information using a questionnaire tool composed  Of (43) items, it was divided into internal sub-variables (within the company), which included (demand management, reliance on customer reaction, value added to the supply chain, response time to customer requests, warehouse management) and external sub-variables (outside the company) that were measured by ( Managing the relationship with suppliers (external supply partners), (managing the relationship with the customer (customer orientation), physical distribution), and included the sub-variables of the dependent variable (performance of the operations system) with (quality, cost, flexibility, and delivery). As for the quantitative approach, it is measured with data. Quantitative using statistical methods (arithmetic mean and standard deviation) by analysis based on the SPSS program , In order to test the hypotheses of influence and correlation, the application program (SMART PLS) will be used, and the extent to which the independent variable (supply chain integration) explains it and its dimensions from the variance occurring in the dependent variable (operations management system performance) will be identified. Then the influence factor and correlation between the variables will be estimated. The study reached several results, the most notable of which is the presence of a significant and positive influence relationship of supply chain integration on the performance of the operations management system. This assumes that supply chain integration is a real function of the performance of the operations management system. Any increase in the (independent variable) will lead to a similar increase in the (dependent variable). The most important recommendations are: defining the company’s vision and mission as to how interaction will be created between the organization’s resources and then transforming them into products that aim to match the design specifications on the one hand and achieve consumer satisfaction on the other hand. second The operations strategy must be based on crystallizing its message in the form of competitive advantage.